The usefulness of a duplex RT-qPCR during the recent yellow fever brazilian epidemic: surveillance of vaccine adverse events, epizootics and vectors - Queiroz, Alice Louize Nunes (MDPI, 2021)
Abstract: From 2016 to 2018, Brazil faced the biggest yellow fever (YF) outbreak in the last 80 years, representing a risk of YF reurbanization, especially in megacities. Along with this challenge, the mass administration of the fractionated YF vaccine dose in a na?ve population brought another concern: the possibility to increase YF adverse events associated with viscerotropic (YEL-AVD) or neurological disease (YEL-AND). For this reason, we developed a quantitative real time RT-PCR (RT-qPCR) assay based on a duplex TaqMan protocol to distinguish broad-spectrum infections caused by wild-type yellow fever virus (YFV) strain from adverse events following immunization (AEFI) by 17DD strain during the vaccination campaign used to contain this outbreak. A rapid and more accurate RT-qPCR assay to diagnose YFV was established, being able to detect even different YFV genotypes and geographic strains that circulate in Central and South America. Moreover, after testing around 1400 samples from human cases, non-human primates and mosquitoes, we detected just two YEL-AVD cases, confirmed by sequencing, during the massive vaccination in Brazilian Southeast region, showing lower incidence than AEFI as expected.